Optimized power control and efficient energy conservation for topology management of MANET with an adaptive Gabriel graph. (November 2018) - Chaudhry, Rashmi; Tapaswi, Shashikala
Abstract: The dynamic nature of Mobile Ad hoc Networks (MANET) poses many challenges including effective management of scarce resources such as energy. Overall energy consumption of a network depends upon the transmission power of its constituent nodes and decides network lifetime. In this paper, a clustering based scalable topology control method, Optimized Power Control (OPC) is proposed to determine the optimal transmission power of nodes with the help of modified Gabriel Graph (GG) algorithm. OPC is tested for its efficiency in terms of various network parameters such as transmission power, per node energy consumption and network delay. Simulation results show that the proposed scheme is scalable and outperforms the existing schemes such as Local Tree based Reliable Topology (LTRT) and Distributed Power Management (DISPOW) in terms of the above-mentioned network parameters. Additionally, per node power level decision using OPC has been improved by approximately 7% in comparison to LTRT and DISPOW.